2010
DOI: 10.1016/j.jpainsymman.2009.05.018
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Decision Making for Cancer Patients in Different Clinical Settings and the Impact of the LCP

Abstract: Differences in the general focus of care among hospitals, nursing homes, and homes may affect the adequacy of end-of-life decision making for the dying. We studied end-of-life decision-making practices for cancer patients who died in each of these settings and assessed the impact of the Liverpool Care Pathway for the Dying Patient (LCP), a template for care in the dying phase. Physicians and relatives of 311 deceased cancer patients completed questionnaires. The LCP was introduced halfway through the study per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Seven more recent studies showed inconsistencies in what was considered a 'home death', in the measurement of pain and in the groups compared. 50,[54][55][56][57][58][59][60] This highlights the need for greater clarity and consistency in measurement and patient selection.…”
Section: Is Home Care or Home Death Better Than Other Places -For Examentioning
confidence: 99%
“…Seven more recent studies showed inconsistencies in what was considered a 'home death', in the measurement of pain and in the groups compared. 50,[54][55][56][57][58][59][60] This highlights the need for greater clarity and consistency in measurement and patient selection.…”
Section: Is Home Care or Home Death Better Than Other Places -For Examentioning
confidence: 99%
“…12 The LCP is structured around an initial assessment, ongoing care, and care after death. Positive outcomes regarding integrated care pathways (ICP) for EOL care in various settings have been identified 8,[13][14][15][16][17][18][19] although randomized control trials are absent. 13,20 The LCP has been found to improve the plan of care, provide guidance, and improve documentation and communication.…”
Section: Introductionmentioning
confidence: 99%
“…23,32,34,37 Two (50%) reported significant results in favor of the intervention. 32 Four studies reported on do-not-resuscitate and advanced directive status 15,26,35,38 as an outcome of the intervention. Two were RCTs.…”
Section: Other Outcomesmentioning
confidence: 99%